2023
DOI: 10.1136/gutjnl-2022-327924
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 attenuates hepatocarcinogenesis by blocking hypoxia-driven angiogenesis and immunosuppression

Abstract: ObjectiveThe current treatment for hepatocellular carcinoma (HCC) to block angiogenesis and immunosuppression provides some benefits only for a subset of patients with HCC, thus optimised therapeutic regimens are unmet needs, which require a thorough understanding of the underlying mechanisms by which tumour cells orchestrate an inflamed tumour microenvironment with significant myeloid cell infiltration. MicroRNA-223 (miR-223) is highly expressed in myeloid cells but its role in regulating tumour microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Recently, studies in HCC have found that myeloid cells (mainly the monocyte-derived macrophages) expressed PD-L1 play a critical role in regulating the hypoxic tumor microenvironment and immune escape of HCC. 45,46 According to our results, we speculate that through this mechanism PSMCs may be involved in the regulation of the immune response in HCC. CTLA4 inhibition can lead to increased activation of naive CD4 and CD8 T cells by acting on T cell-antigen-presenting cell immune synapse.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, studies in HCC have found that myeloid cells (mainly the monocyte-derived macrophages) expressed PD-L1 play a critical role in regulating the hypoxic tumor microenvironment and immune escape of HCC. 45,46 According to our results, we speculate that through this mechanism PSMCs may be involved in the regulation of the immune response in HCC. CTLA4 inhibition can lead to increased activation of naive CD4 and CD8 T cells by acting on T cell-antigen-presenting cell immune synapse.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, we mainly focus on the regulation of TLR on PD-L1 expression in tumor cells, but tumor-associated macrophage also plays a critical role in the development of HCC. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…focus on the regulation of TLR on PD-L1 expression in tumor cells, but tumor-associated macrophage also plays a critical role in the development of HCC. 31,32 ICD-associated DAMPs activate antitumor immune responses by activating the innate immunity represented by TLR3 and TLR4. 33,34 Interestingly, the expressions of TLR3 and TLR4 increased in lenvatinib-treated cells and played contrasting roles in tumors.…”
mentioning
confidence: 99%
“…The authors proposed an intriguing model for chronic inflammation-associated HCCs in which myeloid cells represent the source for miR-223 transfer to cancer cells, where miR-223 inhibits HIF-1A expression and indirectly influences the composition of the TME by suppressing the HIF-1A-driven CD39/CD73-adenosine pathway that contributes to PD-1 and PD-L1 upregulation in immune cells. Adenovirus-mediated gene delivery of miR-223 in two inflammatory-associated models of HCC hindered tumor development and progression by inhibiting angiogenesis and hypoxia-mediated PD1/PD-L1 activation in T cells and macrophages, proving the therapeutic potential of miR-223 in blocking the immunosuppressive tumor microenvironment in HCC [109]. Notably, "RNA-RNA" crosstalk relies not only on noncoding RNAs functioning as "microRNA sponges" but also on coding mRNAs, which can relieve the inhibitory effect of miRNAs on their target genes by ceRNA activity.…”
Section: Noncoding Rnas Affect Immunotherapy Response By Mediating Ce...mentioning
confidence: 99%